Bi25FeO40/Bi2O2CO3 piezoelectric catalyst with built-in electric fields that was prepared via photochemical self-etching of Bi25FeO40 for 4-chlorophenol degradation. (20th March 2022) - Jiang, Tingjin; Wang, Yang; Guo, Zichang; Luo, Haopeng; Zhan, Chuanxiang; Wang, Yaojin; Wang, Zhe; Jiang, Fang; Chen, Huan
Abstract: Piezoelectric catalysis based on the polarization of piezoelectric materials is a promising technology for environmental pollutant treatment. Developing effective piezoelectric catalysts and clarifying the reaction mechanism are crucial to the application of piezoelectric catalysis. Herein, a unique strategy of photochemical self-etching of Bi25 FeO40 was used to prepare a piezoelectric catalyst of Bi25 FeO40 /Bi2 O2 CO3 . During the photochemical process, methanol was oxidized to formaldehyde, and then Bi species on the surface of Bi25 FeO40 reacted with formaldehyde to form Bi2 O2 CO3 . As a lead-free piezoelectric catalyst, the Bi25 FeO40 /Bi2 O2 CO3 composite possessed excellent activity for the degradation of 4-chlorophenol under ultrasonic vibration, and the degradation efficiency was more than 90% within 120 min. Introducing Bi2 O2 CO3 onto the surface of Bi25 FeO40 can significantly promote the piezoelectric catalytic activity of Bi25 FeO40 via the effect of built-in electric fields. It was also found that ·OH and ·O2 − are the main active species that are responsible for the degradation of 4-CP. The results that are presented here can extend the piezoelectric application of bismuth ferrate, and the strategy for building up the heterojunction is helpful for the preparation of other Bi-containing piezoelectric catalysts. Graphical abstract: Image 1 Highlights: Photochemical self-etching strategy was used for the generation of formaldehyde to fabricate Bi25 FeO40 /Bi2 O2 CO3 heterojunctions. Bi25 FeO40 /Bi2 O2 CO3 composite was found to be attractive as a lead-free piezo piezoelectric catalyst with high activity of 4-CP degradation. Introduction of Bi2 O2 CO3 promoted the piezoelectric catalytic activity of Bi25 FeO40 via the effect of built-in electric fields.